Locking Crops to Unlock Investment : Experimental Evidence on Warrantage in Burkina Faso - Delavallade, Clara; Godlonton, Susan (World Bank, Washington, DC, 2020)
Financial market imperfections remain pervasive in developing countries, constraining potentially profitable investment decisions, especially for rural smallholder farmers. Warrantage is an innovative model of rural finance with the potential to overcome credit, storage, and commitment constraints through a localized inventory credit scheme. Exploiting random variations in household access to warrantage and intensity of access across villages, this paper studies the direct impact of this scheme on beneficiaries as well as its spillover effects. Take-up of storage is high (94 percent), while credit take-up is moderate (38 percent). Households with access to warrantage primarily store sorghum and maize and sell their production over an extended period of time, earning higher average prices and resulting in higher sales revenue ($248, or 33 percent, on average). Increased incomes are spent on long-term investments, including human capital expenditures (education), livestock purchases, and investment in agricultural inputs for the subsequent year.